2021
DOI: 10.1186/s13756-020-00869-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of florfenicol resistance genes in the coagulase-negative Staphylococcus (CoNS) isolates and genomic features of a multidrug-resistant Staphylococcus lentus strain H29

Abstract: Background With the wide use of florfenicol to prevent and treat the bacterial infection of domestic animals, the emergence of the florfenicol resistance bacteria is increasingly serious. It is very important to elucidate the molecular mechanism of the bacteria’s resistance to florfenicol. Methods The minimum inhibitory concentration (MIC) levels were determined by the agar dilution method, and polymerase chain reaction was conducted to analyze the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(26 reference statements)
1
11
0
2
Order By: Relevance
“…This species is considered an animal pathogen and has been detected among livestock, pets, wild animals and retail meats [13,16,34,35]. Nevertheless, S. lentus has also been responsible for a wide range of human infections and its clinical relevance seems to be increasing [36]. S. urealyticus was the second most common CoNS species found in poultry and it was mostly detected in quail samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is considered an animal pathogen and has been detected among livestock, pets, wild animals and retail meats [13,16,34,35]. Nevertheless, S. lentus has also been responsible for a wide range of human infections and its clinical relevance seems to be increasing [36]. S. urealyticus was the second most common CoNS species found in poultry and it was mostly detected in quail samples.…”
Section: Discussionmentioning
confidence: 99%
“…PEN 11 , FOX 4 , CIP 11 , CN 2 , TOB 14 , KAN 9 , ERY 35 , CD 36 , TET 25 , C 4 , FD 12 , SXT 6 mecA 36 , ermA 8 , ermB 8 , ermC 28 , mphC 29 , aph(3 )-IIIa 9 , ant(4 )-Ia 12 , str 2 , tetL 19 , tetK 14 , tetO 1 , tetM 2 , cat p194 1 , dfrK 6 , dfrD 2 S. urealyticus 21 PEN 21 , FOX 18 , CIP 3 , CN 4 , TOB 6 , KAN 5 , ERY 21 , CD 21 , TET 21 , C 3 , FD 17…”
Section: S Lentus 36unclassified
See 1 more Smart Citation
“…6 (AB), showed that the average diameters of the nanoparticles were 4553. nm and that 10% of the particles had diameters of 40.00 nm, while 50% had diameters of 50.00 nm, while 90% Their diameters were 60.00 nm, and the same figure represents a miniature table of the diameters and size of those nanoparticles whose diameter ranged between (30-65) nm and a description of the accumulation of these nanoparticles, which were clarified in a graph representing the relationship between the diameter of the nanoparticle and the percentage represented by the cumulative distribution of the particles As shown in Figs. (1)(2)(3)(4)(5)(6)(7), the shape of silver nanoparticles is shown, as the homogeneous structure of the nanoparticles is clear, and how the nanoparticles are lined up in one line side by side in an orderly, visible three dimensional manner. As for Fig.…”
Section: Production and Characterization Of Silver Agnps Nanoparticlesmentioning
confidence: 99%
“…If it produces secondary metabolic compounds, including alkaloids, flavonoids, saponin, anti-oxidants, anti-inflammatory, anti-diabetic, and other medically important secondary compounds, especially in the leaves of the tree [3]. Also, the synthetic silver nanoparticles AgNPs nanoparticles are considered a promising generation of antibiotics, as these particles have activity against cancer cells and bacteria, as they are used against Gram-positive and Gramnegative bacteria [4] [5]. These particles are considered to have an inhibitory effect on bacteria, especially those bacteria that are resistant to antibiotics, this resistance was considered a major health problem [6].…”
Section: Introductionmentioning
confidence: 99%